Efficacy and Safety of Direct-Acting Antiviral Therapy in Patients With Chronic Hepatitis C Virus Infection: A Real-World Single-Center Experience in Tianjin, China - Xia, Huan; Lu, Chengzhen; Wang, Yin; Zaongo, Silvere D.; Hu, Yue; Wu, Yue; Yan, Zhongfang; Ma, Ping (Frontiers in Pharmacology, 2020)
Objective Toward the limited real-world data concerning the treatment response to brand direct-acting antiviral agents (DAAs) therapy, we proposed to evaluate the efficacy and safety of DAAs for the treatment of chronic hepatitis C virus (HCV) in mainland China. Methods In this retrospective, single-center, cohort study, all HCV-infected adult patients treated with brand DAA drugs covered by Tianjin local health insurance (Apr 2018–Sept 2019) and responding to other specific inclusion criteria were recruited. The five available DAA regimens included sofosbuvir + ribavirin (SOF + RBV), elbasvir/grazoprevir (EBR/GZR), ombitasvir/paritaprevir/ritonavir/dasabuvir (OBV/PTV/r/DSV) ± RBV, daclatasvir + asunaprevir (DCV + ASV), and SOF + DCV ± RBV. Demographic, virologic, clinical, and adverse effects data obtained during and after DAAs treatment were collected. We evaluated the rate of sustained virological response at 12 weeks post-treatment (SVR12), the incidence of adverse effects, and assessed the factors associated with SVR12. Results Four hundred ninety-four patients finished the treatment and completed the 12-week post-treatment follow-up. The overall SVR12 rate was estimated at 96.96%. SVR rates greater than 95% were achieved in most of the HCV genotypes with the exception of GT1a (0%), GT3a (93.33%), and GT3b (88.24%). SVR12 for patients treated with DCV + ASV, EBR/GZR, OBV/PTV/r/DSV ± RBV, SOF + DCV ± RBV, and SOF + RBV for 12 or 24 weeks was 86.67%, 100%, 98.11%, 97.56%, and 95.06%, respectively. Subjects with compensated cirrhosis (92.73%) and prior treatment experience (77.78%) had significantly lower SVR rates when compared to chronic hepatitis C (98.15%) and treatment-naive (97.69%) groups. In Tianjin, the available DAA regimens were generally well-tolerated, and not a single serious adverse event was reported. Conclusion In this large real-life single-center HCV cohort from China, oral DAAs were highly effective and well-tolerated. Further and larger-scale studies are needed to evaluate their clinical safety and efficacy.